Applicability of the Calce method for age estimation in an Indian population: A clinical CT-based study. (November 2022) - Warrier, Varsha; Shedge, Rutwik; Garg, Pawan Kumar; Dixit, Shilpi Gupta; Krishan, Kewal; Kanchan, Tanuj
Highlights: Calce method is proposed as a tool for age estimation from the acetabulum. The present study tests the applicability of Calce method in an Indian population. Morphological features defined by Calce can be easily visualized on CT scans. Calce method yielded lower accuracy in those aged 40 years and above for the study population. Lack of applicability of Calce method can be attributed to the broad age ranges it uses. Abstract: Age estimation is one of the prerequisites of human identification. Age-progressive changes in the pelvis offer useful evidence for forensic age estimation across all age groups. The acetabulum presents as a durable and taphonomic degradation resistant age marker, and, can be employed for analysing age-progressive changes described by Calce. The present study aimed at determining the applicability of the Calce method for age estimation in an Indian population based on a computed tomographic examination of the acetabulum. Additionally, different morphological features defined by Calce were evaluated to identify the feature which contributes most towards the process of age estimation. CT images obtained from clinically undertaken examinations of individuals aged 17 years and above were scrutinized according to the features defined within the Calce method. No statistically significant bilateral or sex differences were observed. An overall accuracy of 76.66% was observed on applying the Calce method to an Indian population, with lower accuracy percentages for individuals aged 40 years and above. The associated overall inaccuracy and bias were found to be 9.45 and 8.88 years, respectively. Within the various features, acetabular groove was found to contribute most towards the overall accuracy, and apex growth the least. Considering this weighted proportion, population specific models should be derived to render greater applicability to the method for age estimation.